2022
DOI: 10.3390/ijms231911320
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Endocrine Disruptor Vinclozolin Leads to Lung Damage via Nrf2–Nf-kb Pathway Alterations

Abstract: Endocrine-disrupting substances (EDS) are common and pervasive in our environment and pose a serious risk to both human and animal health. Endocrine-disrupting compounds (EDCs) have been associated with a variety of detrimental human health effects, including respiratory issues, as a result of their ability to disrupt cell physiology. Vinclozolin ((RS)-3-(3,5-Dichlorophenyl)-5-methyl-5-vinyloxazolidine-2,4-dione) is a common dicarboximide fungicide used to treat plant diseases. Several studies have analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
(89 reference statements)
2
7
0
Order By: Relevance
“…Most of the studies on VCZ focus mainly on the reproductive system. The VZN toxicity is often associated with increased oxidative stress, for example when ingested in excessive amounts and repeatedly in fish models [ 20 , 21 ]. Previous studies have shown a link between pesticide exposure and cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies on VCZ focus mainly on the reproductive system. The VZN toxicity is often associated with increased oxidative stress, for example when ingested in excessive amounts and repeatedly in fish models [ 20 , 21 ]. Previous studies have shown a link between pesticide exposure and cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity effects from prolonged exposure to VCZ have been well documented. In fact, previous studies have shown how 28-day VCZ exposure can cause histological alteration and fibrosis in several organs such as lung and kidney on mouse [ 20 , 21 ]. The long-term damage caused by VCZ can be even greater, such as damage at behavioral level, affiliative behavior, or motor inhibition in mammals, but also in different class of animals like birds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example are endocrine disruptors, which are part of plastics (“microplastics”, for example Bisphenol A) or are used as fungicides in agriculture (for example, Vinclozolin). These substances not only have an impact on the reproductive system, but also other organs including the lung by affecting Nrf2/NF-ΚB pathways [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, VIN effects on the endocrine system have been reported, evidencing altered male reproduction as the main effect, inducing a lower sperm quality and number, epididymal morpholohical changes, and prostate abnormalities (Anway and Skinner 2008 ; Paoloni-Giacobino 2014 ; Feijó et al 2021 ). Regarding the action on the immune system, only few information are available, namely its ability to interact with NF-κB and with lymphocyte activity, increasing T and B cells percentage, while decreasing NK cells (White et al 2004 ; D’Amico et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%